2020
DOI: 10.1093/mnras/staa2987
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from APOGEE for the presence of a major building block of the halo buried in the inner Galaxy

Abstract: We report evidence from APOGEE for the presence of a new metal-poor stellar structure located within ∼4 kpc of the Galactic Centre. Characterized by a chemical composition resembling those of low-mass satellites of the Milky Way, this new inner Galaxy structure (IGS) seems to be chemically and dynamically detached from more metal-rich populations in the inner Galaxy. We conjecture that this structure is associated with an accretion event that likely occurred in the early life of the Milky Way. Comparing the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
230
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(254 citation statements)
references
References 125 publications
24
230
0
Order By: Relevance
“…Accreted stars selected via their chemistry (orange) show a large distribution of energies (−1.61 +0.22 −0.26 × 10 5 km 2 s −2 ). Comparing these values with those by Horta et al (2021), who used the same gravitational potential (McMillan 2017) within the same orbit calculation code GALPY (Bovy 2015;Mackereth & Bovy 2018) suggests a non-negligible overlap with the Inner Galaxy Structure (IGS) / Heracles they identified (Horta et al 2021). In a similar manner, we find most members of the GSE (79 per cent) tend to have orbit energies above −1.8 × 10 5 km 2 s −2 .…”
Section: Stellar Kinematics/dynamicssupporting
confidence: 75%
“…Accreted stars selected via their chemistry (orange) show a large distribution of energies (−1.61 +0.22 −0.26 × 10 5 km 2 s −2 ). Comparing these values with those by Horta et al (2021), who used the same gravitational potential (McMillan 2017) within the same orbit calculation code GALPY (Bovy 2015;Mackereth & Bovy 2018) suggests a non-negligible overlap with the Inner Galaxy Structure (IGS) / Heracles they identified (Horta et al 2021). In a similar manner, we find most members of the GSE (79 per cent) tend to have orbit energies above −1.8 × 10 5 km 2 s −2 .…”
Section: Stellar Kinematics/dynamicssupporting
confidence: 75%
“…This insight has allowed the unravelling of the assembly history of the Galaxy through its GC population (e.g. Kruijssen et al 2020), and predicted early accretion events which have recently been confirmed with the discovery of its stellar debris (Horta et al 2020a).…”
mentioning
confidence: 90%
“…Through careful chemodynamical dissection, the bulge has been found to contain stars that are part of the bar, inner thin, and thick disks, as well as a pressuresupported component (Queiroz et al 2020a). Furthermore, there is evidence that the bulge also contains a remnant of a past accretion event, the inner Galaxy structure (Horta et al 2021). Multiple age studies of the bulge have reported that while the bulge is mainly composed of old stars (∼10 Gyr), it contains a nonnegligible fraction of younger stars (Bensby et al 2013(Bensby et al , 2017Schultheis et al 2017;Bovy et al 2019;Hasselquist et al 2020).…”
Section: Introductionmentioning
confidence: 99%